2020
DOI: 10.21037/atm-20-3200
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of the quality of clinical practice guidelines for idiopathic pulmonary fibrosis

Abstract: Background: Clinical practice guidelines (CPGs) have long served as an essential tool for clinicians to rationalize their treatment in practice. However, the quality of guidelines varies greatly. The present study aimed to analyze high-quality CPGs of idiopathic pulmonary fibrosis (IPF) and highlight the potential for further improvement. Methods: Three guideline developers' websites, PubMed, Embase, and Web of Science, as well as a public search engine, Google Scholar, were searched to retrieve CPGs regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Understanding the purpose of the RIGHT checklist is necessary to assist CPG developers in reporting CPGs, to support peer reviewers in considering CPG reports, and to assist clinicians in understanding and implementing CPGs. Therefore, it is important to improve the quality of CPG reporting during the production or revision of CPGs in the future [ 62 ]. Among the seven domains of the RIGHT scale, Domain 4 (‘recommendations’) had the highest reporting rate, while Domain 5 (‘rationale/explanation for recommendations’) had the lowest reporting rate.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the purpose of the RIGHT checklist is necessary to assist CPG developers in reporting CPGs, to support peer reviewers in considering CPG reports, and to assist clinicians in understanding and implementing CPGs. Therefore, it is important to improve the quality of CPG reporting during the production or revision of CPGs in the future [ 62 ]. Among the seven domains of the RIGHT scale, Domain 4 (‘recommendations’) had the highest reporting rate, while Domain 5 (‘rationale/explanation for recommendations’) had the lowest reporting rate.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only a limited number of CPGs described the details of external review, and none of the CPGs reported the quality assurance process. The finding is 11b If the guideline developers used existing systematic reviews, reference these and describe how those reviews were identified and assessed (provide the search strategies and the selection criteria, and describe how the risk of bias was evaluated) and whether they were updated in line with previously published studies on other diseases, such as idiopathic pulmonary fibrosis (31). If the review process is poorly reported, it is not possible to determine if and how the review was used to improve the guideline and its recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the AGREE II procedure, a CPG's recommendation status is not based on an overall score. According to the classi cation used in prior research7, CPGs in this study were suggested if they scored above 50% in more than four domains [11][12][13] .…”
Section: Methodological Quality Assessment Of Guidelinesmentioning
confidence: 99%